Fibrinogen Supplementation and Its Indications - Grottke, Oliver; Mallaiah, Shuba; Karkouti, Keyvan; Saner, Fuat; Haas, Thorsten (Seminars in Thrombosis and Hemostasis, 2020)
Adequate plasma levels of fibrinogen are essential for clot formation, and in severe bleeding, fibrinogen reaches a critically low plasma concentration earlier than other coagulation factors. Although the critical minimum concentration of fibrinogen to maintain hemostasis is a matter of debate, many patients with coagulopathic bleeding require fibrinogen supplementation. Among the treatment options for fibrinogen supplementation, fibrinogen concentrate may be viewed by some as preferable to fresh frozen plasma or cryoprecipitate. The authors review major studies that have assessed fibrinogen treatment in trauma, cardiac surgery, end-stage liver disease, postpartum hemorrhage, and pediatric patients. Some but not all randomized controlled trials have shown that fibrinogen concentrate can be beneficial in these settings. The use of fibrinogen as part of coagulation factor concentrate based therapy guided by point-of-care viscoelastic coagulation monitoring (ROTEM [rotational thromboelastometry] or TEG [thromboelastography]) appears promising. In addition to reducing patients' exposure to allogeneic blood products, this strategy may reduce the risk of complications such as transfusion-associated circulatory overload, transfusion-related acute lung injury, and thromboembolic adverse events. Randomized controlled trials are challenging to perform in patients with critical bleeding, and more evidence is needed in this setting. However, current scientific rationale and clinical data support fibrinogen repletion in patients with ongoing bleeding and confirmed fibrinogen deficiency.
Keywords: coagulopathy; fibrinogen; hemorrhage; perioperative